Expressão de ZAP 70 e relação com a expressão de CD 38, ploidia e índice de fase S em pacientes com lucemia linfocítica crônica - Dametto, Ana Paula Fortunato [UNESP] (2014)
The Chronic Lymphocytic Leukemia (CLL) is a mature B lymphocytes malignancy, on heterogeneous clinical course, where some patients require immediate treatment and others live for decades without treatment. For this peculiarity, it’s required the identification of prognostic markers and clinical value. The main objective was to retrospectively, evaluate the prognostic indicator of the disease progression (ZAP- 70, CD38, DNA ploidy and S phase) in patients under CLL, facing the clinical evolution. As secondary purposes, methodologies were compared to ZAP- 70 analysis by flow cytometry (FC) ISO Method and Single-Tube Analysis, as well as technical analysis of DNA content by the mathematical model (ModFit LT ™) and boolean gating principle (Infinicyt ™ ). On the registration of the cases observed, there were included 27 patients under the clinical and laboratory data who had available and filled in the term consenting agreement. The evaluation of the clinical situation was made only once, and the results of expressions and CD38 and ZAP 70, were held by reviewing medical records. The analysis of DNA content by CF was evaluated by the above two methods files from a laboratorial flow cytometry institution. As a result, no relation of the expressions of CD38 and ZAP- 70 with the clinical status of the patients was observed. Concerning the analysis of DNA index and S phase, there wasn’t any statistical difference (p = 0.69 and p = 0.08 respectively using the ModFit LT ™ and Infinicyt ™ software ). It was also found that the data obtained in the analysis of DNA indicates the possibility of using the S phase in the prognostic evaluation of those patients. Conclusion: all the three factors studied are considered prognostic. There was no relation of the markers studied to the clinical course of patients. To correlate these data with clinical follow-up of those patients, it is necessary a longer period of time